Facile synthesis of gelatin‐protected silver nanoparticles for SERS applications. (24th April 2013) - Lee, Changwon; Zhang*, Peng
Abstract : Gelatin‐protected silver nanoparticles have been synthesized by a one‐pot, green method for surface‐enhanced Raman scattering (SERS) applications using gelatin as the reducing and stabilizing agent. The gelatin protection on silver nanoparticle surface helps improve its stability greatly and water dispersibility, while retaining high SERS activity of silver nanoparticles. The gelatin‐protected silver nanoparticles showed SERS signals as low as 100 nM of the typical Raman reporter molecules, RuBPY and R6G and 10 μM of other molecules of interest, melamine and folic acid. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Gelatin‐protected silver nanoparticles have been synthesized by a one‐pot, green method for surface‐enhanced Raman scattering (SERS) applications. The gelatin protection on silver nanoparticle surface helps improve its stability greatly and water dispersibility, while retaining high SERS activity of silver nanoparticles.